Business ethics - Padilla, Reynaldo A. (Manila, Philippines : Rex Book Store, 2004)
This book is to underscore the importance of ethical decision making for you, personally and for your company/business enterprise and to clarify what a significant role in the future manager play in creating an ethical working environment.
CHAPTER 1. The basic of ethics -- 2. Principles and forces that shape ethical behavior -- 3. Responsibilities of the corporation -- 4. The Responsibilities of an employee -- 5. Ethical considerations in relating with peers -- 6. Responsibility to consumers -- 7. The cost of unethical behavior -- 8. Creating an ethical working environment -- 9. Designing a life plan for the future.
Includes bibliographical references and index.
Keywords: BUSINESS ETHICS